Unraveling the ecological processes modulating the population structure of Escherichia coli in a highly polluted urban stream network - Saraceno, Martín (2021)
Escherichia coli dynamics in urban watersheds are affected by a complex balance among external inputs, niche modulation and genetic variability. To explore the ecological processes influencing E. coli spatial patterns, we analyzed its abundance and phylogenetic structure in water samples from a stream network with heterogeneous urban infrastructure and environmental conditions. Our results showed that environmental and infrastructure variables, such as macrophyte coverage, DIN and sewerage density, mostly explained E. coli abundance. Moreover, main generalist phylogroups A and B1 were found in high proportion, which, together with an observed negative relationship between E. coli abundance and phylogroup diversity, suggests that their dominance might be due to competitive exclusion. Lower frequency phylogroups were associated with sites of higher ecological disturbance, mainly involving simplified habitats, higher drainage infrastructure and septic tank density. In addition to the strong negative relationship between phylogroup diversity and dominance, the occurrence of these phylogroups would be associated with increased facilitated dispersal. Nutrients also contributed to explaining phylogroup distribution. Our study proposes the differential contribution of distinct ecological processes to the patterns of E. coli in an urban watershed, which is useful for the monitoring and management of fecal pollution.